Encapsulation of bioactive compounds extracted from date palm seeds (Phoenix dactylifera L.) and their use in functional food - Hashim, Mahmood A.; Huang, Xin; Nadtochii, Liudmila A.; Baranenko, Denis A.; Boulkrane, Mohamed Said; El-Messery, Tamer M. (Frontiers in Nutrition, 2022)
Liposomes have been used as a novel phytoconstituent delivery system to encapsulate lyophilized palm seed phenolic extract (PSPE) and incorporate it into yogurt as a food model to enhance the bioavailability of PSPE. Phenolic compounds were extracted with aqueous ethanol from palm seed powder using the solvent-maceration approach assisted by ultrasonication. Lyophilized PSPE (0.2–1% w/v) was enclosed in a liposome structure coated with or without chitosan (primary/secondary liposome). Particle size, zeta potential, encapsulation efficiency (EE), Fourier transform infrared spectroscopy (FTIR), and transmission electron microscopy (TEM) were applied to investigate the primary and secondary liposomes. To assess the in vitro bioaccessibility of PSPE and primary/secondary liposomes, the total phenolic content (TPC) and the antioxidant activity were studied during the oral, gastric, and intestinal digestion stages. Three concentrations of lyophilized secondary liposomes (1.25, 2.5, and 3.75% w/v) were added to the yogurt food model. During the 14 days of storage, the physical, chemical, and sensory properties were assessed. Compared to the primary liposomes (87%), the secondary liposomes (91%) showed a higher encapsulation efficiency. Comparing the secondary liposomes to the original liposomes and the non-encapsulated PSPE, the bioaccessibility of phenolic compounds was improved. Fortified yogurt with secondary liposomes had a lower syneresis and viscosity than the reference yogurt. The encapsulated PSPE provided a good level of protection, and its release increased throughout the intestinal phase. Thus, PSPE in a microencapsulated form has been proven to be a rich and cost-effective source of phenolics that can be used successfully to produce functional yogurt.